Criterios de evaluacion en ensayos de herbicidas contra avena loca (Avena spp.) en cereales - Fernandez-Quintanilla, C.=700 1 Navarrete, L.; Torner, C.
(Es, En)
ilus., 11 ref.
Keywords: MALEZAS; ESCARDA; CEREALES; EVALUACION; HERBICIDAS; AVENA FATUA; ESPAÑA